Enantiopure anion templated synthesis of a zeolitic metal–organic framework. Issue 9 (18th December 2015) - Xu, Zhong-Xuan; Ma, Yu-Lu; Zhang, Jian
Abstract : Enantiopure anions were employed as the templates of a GIS-type metal–organic framework with achiral building units. Abstract : Utilizing ( R )-H3 CIA as a chiral template, an unprecedented homochiral metal–organic framework (MOF) with zeotype GIS topology is obtained from achiral 1.4-DIB ligands and Zn(ii ) ions, which opens up a feasible approach to create zeolitic MOFs with homochirality.